PENDIDIKAN KESEHATAN GOOD FOOD, GOOD SLEEP, GOOD MOOD RAHASIA KOMBO HIDUP SEHAT - Bachtiar Safrudin; Kartika Setia Purdani; Cahya Indah Fitriani; Wanda Amelia N.; Cindy Maharani Dewi; Diah Maulia; Diandra Dita Raudina; Fachmi Alamsyah; Indah Prayudita; Naelan Najah; Nur Abida; Putri Sintya Wati; Rifky Rama Nur H.; Tsamarah Hanin Rana; Winna Noor Cholifah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Health significantly influences the learning quality of vocational high school students. However, many of them still have poor dietary habits, insufficient sleep, and difficulty managing their mood. The concept of "Good Food, Good Sleep, Good Mood" serves as a crucial foundation for improving physical and mental balance. Health education interventions are effective measures to help students improve their lifestyle habits. Through counseling, guidance, evidence-based educational materials, and interactive activities, it is expected that students' understanding of the importance of diet, sleep, and emotional management can be enhanced. Questionnaire results at Muhammadiyah 04 Samarinda Vocational High School indicate low consumption of fruits and vegetables, unhealthy eating habits, and poor sleep quality. Based on these conditions, a community service activity was conducted through health education to encourage students to adopt healthy habits and improve their mood and academic performance.